Comparison of lower limb calibration methods for movement analysis with inertial measurement unit (IMU) - Pacher, L.; Chatellier, C.; Vauzelle, R.; Fradet, L. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Wearable sensor makes possible today to obtain motion measurement for health monitoring, physical activity assessment, or sport performance evaluation in ecological environment. One of them, the inertial measurement unit (IMU), is extensively used to obtain measurements relative to human motion. The IMU, composed of 3D gyroscope, accelerometer, and generally magnetometer, can be used to provide an orientation in a global coordinate system after fusion of the different sensor data.